Growth of human mesenchymal stem cells (MSCs) on films of enzymatically modified chitosan. (4th February 2016) - Aljawish, Abdulhadi; Muniglia, Lionel; Chevalot, Isabelle
Abstract : Mesenchymal stem cells (MSCs) are known to be an attractive cell source for tissue engineering and regenerative medicine. One of the main limiting steps for clinical use or biotechnological purposes is the expansion step. The research of compatible biomaterials for MSCs expansion is recently regarded as an attractive topic. The aim of this study was to create new functional biomaterial for MSCs expansion by evaluating the impact of chitosan derivative films modified by enzymatic approach. First, chitosan particles were enzymatically modified with ferulic acid (FA) or ethyl ferulate (EF) under an eco‐friendly procedure. Then, films of chitosan and its modified derivatives were prepared and evaluated by physicochemical and biological properties. Results showed that the enzymatic grafting of FA or EF onto chitosan significantly increased hydrophobic and antioxidant properties of chitosan films. The MSCs cell viability on chitosan derivative films also increased depending on the film thickness and the quantity of grafted phenols. Furthermore, the cytotoxicity test showed the absence of toxic effect of chitosan derivative films towards MSCs cells. Cell morphology showed a well attached and spread phenotype of MSCs cells on chitosan derivative films. On the other hand, due to the higher phenol content of FA‐chitosan films, their hydrophobic, antioxidant properties and cell adhesion were improved in comparison with those of EF‐chitosan films. Finally, this enzymatic process can be considered as a promising process to favor MSCs cell growth as well as to create useful biomaterials for biomedical applications especially for tissue engineering. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:491–500, 2016